Influence of endurance exercise training on antioxidant enzymes, tight junction proteins, and inflammatory markers in the rat ileum. (December 2015) - Holland, A.; Hyatt, Hayden; Smuder, Ashley; Sollanek, Kurt; Morton, Aaron; Roberts, Michael; Kavazis, Andreas
Abstract Background This study investigated the effects of endurance exercise training on ileum antioxidant status, as well as tight junction, inflammatory, and nutrient transporter gene expression. Methods Sprague–Dawley rats (4 month old) were assigned to sedentary (SED) or endurance exercise-training (EXE) groups (n = 8/group). EXE animals were trained on the treadmill for 10 days at a speed of 30 m/min at 0° incline for 60 min/day. SED and EXE animals were sacrificed (24 h after the final training bout) and the ileum was stored for analyses. Results The ileum of EXE had higher (p < 0.05) antioxidant protein levels of manganese superoxide dismutase and catalase compared to SED with no change (p > 0.05) in the lipid peroxidation biomarker 4-hydroxynonenal. Ileum mRNA expression of the tight junction gene zonulin increased (p < 0.05) and claudin 1 decreased (p < 0.05) in EXE compared to SED, but occludin and zonula occluden 1 were not different (p > 0.05) between SED and EXE. The ileum mRNA expressions of seven nutrient transporters (SLC5A8, SLC7A6, SLC6A19, SLC7A7, SLC27A2, SLC16A10, and SLC15A1) were not different between the two groups (p > 0.05). EXE had lower ileum TNFα mRNA expression (p < 0.05) compared to SED. No changes (p > 0.05) were found in the other inflammatory mRNAs including NFκB, IFNγ, IL6, CCL2, TLR4, and IL10. In addition, no changes in p-p65:p65 were detected. Conclusions These findings suggest that 10 days of endurance exercise training up-regulates key endogenous antioxidant enzymes, decreases select inflammation markers, and alters select markers of tight junction permeability.